2018
DOI: 10.5114/ada.2017.71422
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omalizumab treatment on IgE and other immunoglobulin levels in patients with chronic spontaneous urticaria and its association with treatment response

Abstract: IntroductionSuppression of free immunoglobulin E (IgE) levels and an increase in total IgE levels are observed during omalizumab treatment. However, whether omalizumab has any effect on other immunoglobulins is unknown.AimTo investigate the effect of omalizumab treatment on serum IgE and other immunoglobulins, and demonstrate any association with response to treatment in patients with chronic spontaneous urticaria (CSU).Material and methodsThe study included 41 patients diagnosed with CSU. Baseline and post-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The mechanistic reason for the mild effect in neutrophils is unclear and could reflect interference with certain aspects of KIT‐dependent neutrophil differentiation or survival, or indirect modulation of neutrophil tissue distribution as a result of MC suppression. Interestingly, decreases in neutrophil count have also been reported with other approved mAbs that affect MC activity such as the anti‐IgE omalizumab and the anti‐IL4Rα mAb dupilumab 23,58,59 . In addition to its role in hematopoiesis, KIT signaling is important in other processes and has been described to have a role in hair pigmentation and spermatogenesis 31,32,60,61 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mechanistic reason for the mild effect in neutrophils is unclear and could reflect interference with certain aspects of KIT‐dependent neutrophil differentiation or survival, or indirect modulation of neutrophil tissue distribution as a result of MC suppression. Interestingly, decreases in neutrophil count have also been reported with other approved mAbs that affect MC activity such as the anti‐IgE omalizumab and the anti‐IL4Rα mAb dupilumab 23,58,59 . In addition to its role in hematopoiesis, KIT signaling is important in other processes and has been described to have a role in hair pigmentation and spermatogenesis 31,32,60,61 .…”
Section: Discussionmentioning
confidence: 92%
“…with other approved mAbs that affect MC activity such as the anti-IgE omalizumab and the anti-IL4Rα mAb dupilumab. 23,58,59 In addition to its role in hematopoiesis, KIT signaling is important in other processes and has been described to have a role in hair pigmentation and spermatogenesis. 31,32,60,61 Importantly, the data from preclinical models suggest these effects are fully reversible.…”
Section: Cdx-0159inducesdose-dependent Suppression Of Plasma Tryptase...mentioning
confidence: 99%
“…16 Moreover, Çilda g et al found a decrease in the number of neutrophils in urticaria patients receiving omalizumab. 17 SII is one of the newly prognostic biomarker based on platelets, neutrophils, and lymphocytes. The clinical observation studies indicate that SII is a powerful tool for predicting survival outcomes and appears to be a simple and inexpensive tool in the prediction of the progression of a diverse number of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Among other biologics that inhibit Th2 pathways, only omalizumab was associated with alopecia in this study, probably due to the increased total IgE levels after omalizumab use. Omalizumab, an anti-IgE agent, is known to decrease free IgE levels and increase total IgE levels [ 43 , 44 ]. Our disproportionality analysis revealed that, unlike omalizumab, dupilumab induced both hair growth and hair loss.…”
Section: Discussionmentioning
confidence: 99%